Literarno nagrajevanje na primeru kresnika - Perenič, Urška (Jezik in slovstvo, 2014)
The initial part of the discussion provides a theoretical framework for the concept of literary award giving: at the inter-systemic level in the intersection between the cultural field of ritualised forms of the symbolic worshipping of literature and literary science, and at the level of the literary system in the intersection between the practice of literary studies and that of science. A central role is taken by the jury member: on the one hand, he or she is viewed in interaction with other agents of the literary system while, on the other hand, he or she is observed at the level of literary treatment and presented within the process of autonomous and professional decision-making. How professional and objective this process can be is clear from the second part of the discussion, which provides a detailed compilation of the Kresnik Award jury policies over a period of two years. The assessment scales offer an insight into the procedures of literary assessment. The discussion concludes with a consideration of literary award giving as a relevant object of literary studies.
Keywords: Slovene literature; slovenska književnost; romani; literarne nagrade; kresnik; literarno vrednotenje; žirije